REVIEW ARTIKEL : POTENSI LIKOPEN DARI BUAH TOMAT (Solanum lycopersicum L) SEBAGAI ANTIAGING TOPIKAL - Dani Sujana; Diah Wardani; Nurul Nurul (Jurnal Insan Farmasi Indonesia, 2020)
Free radicals are factors responsible for the skin's aging process. As a result of free radicals, there is a loss of electrons from its free electron pair which makes it unstable and highly reactive in its outer orbital. The effect of an odd number of electrons on free radicals, there is electron capture from other molecules around it to achieve stability. Compounds that can ward off free radicals are antioxidants. Likopen is an antioxidant with high content found in tomato fruit. Antioxidant activity of Lycopen potentially as antiaging skin. The mechanism of action of lycopene as an antioxidant that affects the skin is by lowering erythema due to exposure to UV rays and lowering the activity of Matrix Metalloproteinase-1 (MMP-1), where the enzyme is responsible for increasing the degradation of collagen dilution of the dermis. The occurrence of decreased collagen degradation resulted in reduced roughness to the skin.